525. Characteristics of HIV SARS-COV-2 Coinfection in a Highly HIV Seropositive Population in New York City - Willner, Debra M (Open Forum Infect Dis, 2020)
BACKGROUND: The HIV and COVID-19 co-infection prevalence has not been described extensively. Given the high prevalence of HIV positive patients in our population-our Designated AIDS Center (DAC) caters to approximately 600 patients-of which 68% are virally suppressed, this relationship is of great interest. The objectives of this analysis are to report the characteristics of HIV and COVID-19 patients, and to evaluate for any associations of HIV with COVID-19 outcomes. METHODS: Retrospective chart review of all patients admitted with both HIV and confirmed COVID-19. Collected demographics, past medical history, HIV history including therapy, compliance, viral loads, and CD4 counts, and COVID-19 disease course. Evaluate baseline clinical status utilizing the World Health Organization’s Ordinal Scale for Clinical Improvement, and note disease outcomes. Analyzed mortality and disease severity as compared to the general COVID-19 patient population. RESULTS: 39 patients were identified with HIV and COVID-19 from March 15(th) –June 18(th) 2020. Baseline characteristics of these patients are listed in Figure 1. Of the available labs, 60% of patients were virally suppressed, and 87% had CD4+ counts above 200/µL. On admission, most patients either did not require oxygen support, or received support through noninvasive methods. In Figure 2 we see the final outcome of the patients, with 77% of the patients discharged, and a mortality rate of 18%. Of note, the only baseline characteristic that had a significant correlation with mortality among our patients was age > 60 (p = 0.03). Baseline Characteristics of HIV COVID-19 Patients and Pertinent COVID-19 Admission Statistics [Image: see text] COVID-19 Outcomes [Image: see text] CONCLUSION: Mortality in our HIV COVID-19 population was 18%, significantly lower than the 33% in COVID-19 patients overall at our institution. 39 patients with HIV were admitted for confirmed COVID-19 infections, which only amounts to 6.5% of the DAC population, although it is possible that our patients were admitted to other facilities for COVID-19. In our patients, compliance, viral suppression, and CD4+ counts did not correlate with outcomes. Although our mortality was significantly lower than the overall hospital mortality, larger studies are needed to fully evaluate the mortality relationship and determine the protective effects of antiviral therapy and/or decreased immune response in HIV patients with COVID-19. DISCLOSURES: All Authors: No reported disclosures